Aneurysmal subarachnoid hemorrhage in Germany between 2005 and 2018: A nationwide observational study. (5th July 2022) - Uhl, Christian; Huscher, Doerte; Sommerfeld, Jenny; Schönberg, Benn; Vajkoczy, Peter; Dengler, Nora F.
Abstract: Background and purpose: In recent decades, the global incidence of aneurysmal subarachnoid hemorrhage (aSAH) has declined. However, significant regional differences exist. We present the first comprehensive analysis of time trends in the incidence of aSAH and case fatality in Germany. Methods: All patients hospitalized with aSAH in Germany between 2005 and 2018 were identified using International Classification of Disease, 10th Revision codes I60.0–I60.7. Results: A total of 101, 105 cases were included. The incidence of aSAH in Germany decreased at a mean annual rate of 0.5% ( p = 0.003) from 8.9 per 100, 000 population in 2005 to 8.2 in 2018. Over time, incidences of aSAH declined among patients younger than 55 years and patients aged 70–79 years, increased among ages 60–64 years, and remained stable in age groups 65–69 and 85–89 years. This corresponded to an increase in the mean age of aSAH onset from 55.6 (±14.3) to 59.0 (±14.0) years. Throughout the study period, the mean age of aSAH onset was higher in women compared to men (58.3 ± 14.4 years vs. 56.1 ± 14.1 years). There were no changes in in‐hospital case fatality (16.2 vs. 16.6%, p = 0.18), but the duration of hospital stay increased significantly from 19.7 to 24.8 days ( p < 0.001). The most frequent aSAH‐associated aneurysm location was the anterior circulation throughout the entire study period. Conclusions: In Germany, the incidence of aSAH decreased between 2005 and 2018, especially in younger parts of the population. This may reflect effects of lifestyle adjustments most pronounced in younger age groups. Abstract : We analyze nationwide age‐specific incidences of aneurysmal subarachnoid hemorrhage (aSAH) in Germany over the period 2005–2018. The number of patients hospitalized with aSAH decreased over time, especially in younger parts of the population. Hospitalized patients were older and had stable case fatality rates but longer hospital stays over time.